1992
DOI: 10.1172/jci115551
|View full text |Cite
|
Sign up to set email alerts
|

Differences in glucose recognition by individual rat pancreatic B cells are associated with intercellular differences in glucose-induced biosynthetic activity.

Abstract: In vitro incubated rat islet B cells differ in their individual rates of protein synthesis. The number of cells in biosynthetic activity increases with the glucose concentration. Flow cytometric monitoring of the cellular redox states indicated that islet B cells differ in their individual metabolic responsiveness to glucose. A shift from basal to increased NAD(P)H fluorescence occurred for 18% of the cells at 1 mM glucose, for 43% at 5 mM, and for 70% at 20 mM. The functional significance of this metabolic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
156
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 21 publications
7
156
0
1
Order By: Relevance
“…First, we show that within intact rat islets, β cells are heterogenous in their exocytotic activity following glucose stimulation, such that only a subpopulation of β cells displays robust secretion at any one time. The above findings may reflect the metabolic heterogeneity of individual β cells (34), possibly attributable to differences in the expression of "glucose-sensing" enzymes, notably glucokinase (35), and the heterogeneity in glucose-induced cytosolic Ca 2+ ([Ca 2+ ] i ) increases previously observed in 11% of WT mouse islets (36). Interestingly, our results showed that rat β cells manifesting robust GSIS tended to aggregate in small clusters and that cells within individual clusters appeared to act together as a "secretory unit" to release insulin in synchrony.…”
Section: Discussionmentioning
confidence: 71%
“…First, we show that within intact rat islets, β cells are heterogenous in their exocytotic activity following glucose stimulation, such that only a subpopulation of β cells displays robust secretion at any one time. The above findings may reflect the metabolic heterogeneity of individual β cells (34), possibly attributable to differences in the expression of "glucose-sensing" enzymes, notably glucokinase (35), and the heterogeneity in glucose-induced cytosolic Ca 2+ ([Ca 2+ ] i ) increases previously observed in 11% of WT mouse islets (36). Interestingly, our results showed that rat β cells manifesting robust GSIS tended to aggregate in small clusters and that cells within individual clusters appeared to act together as a "secretory unit" to release insulin in synchrony.…”
Section: Discussionmentioning
confidence: 71%
“…Our discovery that a population of immature beta cells persists in the islets of healthy adult mice and, possibly, humans, is also a strong testament to the significant heterogeneity that has long been known amongst beta cells (Giordano et al, 1991;Kiekens et al, 1992). Insulin-expressing Pancreatic Multipotent Progenitor cells (PMPs) were reported that are capable of extensive self-replication, self-renewal and contribute to multiple pancreatic and neural cell types (Smukler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, beta cell heterogeneity was also observed in terms of metabolic, signalling [27,28] and biosynthetic activities [12,29]. Mechanisms explaining heterogeneity of beta cells are totally unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of homologous contacts between beta cells is further supported by the observation in rodents that the functioning of isolated beta cells is heterogeneous [9][10][11][12][13]. For instance, beta cells respond unequally to glucose stimulation in terms of insulin secretion and biosynthetic activity [12,14,15].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation